2023
DOI: 10.3389/fnut.2023.1210215
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of pea protein and whey protein on the metabolic profile of soccer athletes: a randomized, double-blind, crossover trial

Luiz Lannes Loureiro,
Tathiany Jéssica Ferreira,
Fábio Luiz Candido Cahuê
et al.

Abstract: IntroductionPea protein (PP) concentrate is a plant-based alternative to animal protein sources, such as whey protein (WP). In addition to its valuable amino acid composition, PP has a low environmental impact, making it a sustainable, nutritious, and viable alternative for enhanced sports performance, such as in soccer. PP Therefore, this study aimed to evaluate the effects of PP and WP supplementation on biochemical and metabolic parameters in soccer players.MethodsTwelve male under-20 soccer players were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Other researchers [167][168][169][170] demonstrated that ingestion of whey and pea protein produces similar outcomes in measurements of body composition, muscle thickness, force production and strength. Moon et al [171] stated that intake of rice or whey protein in combination with an eight-week resistance training programme led to similar changes in body composition and performance outcomes.…”
Section: An Overview Of Original Scientific Articlesmentioning
confidence: 93%
“…Other researchers [167][168][169][170] demonstrated that ingestion of whey and pea protein produces similar outcomes in measurements of body composition, muscle thickness, force production and strength. Moon et al [171] stated that intake of rice or whey protein in combination with an eight-week resistance training programme led to similar changes in body composition and performance outcomes.…”
Section: An Overview Of Original Scientific Articlesmentioning
confidence: 93%